Effect of mixtures of xanthan gum, modified starch and carrageenan on the apparent viscosity and general acceptability of milk pasteurized flavored whit alkaline cocoa (Agroindustrial Science, 2022)
In this investigation, the effect of mixtures of xanthan gum, modified starch and carrageenan (0% - 0.5%) on the apparent viscosity and general acceptability of milk pasteurized flavored whit alkaline cocoa was evaluated. An extended centroid simplex mixture design was applied, in order to obtain the appropriate mathematical model to represent the behavior of the variables under study and establish the optimal predicted combination of factors that allows optimizing the responses. There was a significant effect (p < 0.05) of the mixture of xanthan gum, modified starch and carrageenan on the apparent viscosity and general acceptability, being the special cubic mathematical model the one that allowed to represent the behavior of both response variables. The predicted optimal mixture of xanthan gum (0.042%), modified starch (0.034%) and carrageenan (0.424%) allowed optimization of the response variables: apparent viscosity (217.76 mPa.s) and general acceptability (7.04, approximate value of 7 = qualification from “I like it moderately”) in milk pasteurized flavored whit alkaline cocoa. The result of this research provides relevant information for the food engineer in the design and development of food products.
Keywords: flavored pasteurized milk; xanthan gum; modified starch; carrageenan; mix design; apparent viscosity; general acceptability